Pendampingan Desa Digital melalui Pembuatan dan Pelatihan Aplikasi SALAD GM Berbasis Website - Mutaqin, Ejen Jenal; Nugraha, Yopi; Hidayat, Dian (IPI Press, 2023)
The Regional Government of West Java Province initiated the Digital Village Program to overcome the problem of digitalization inequality between rural and urban communities with the aim of facilitating village governments to carry out various innovations in facing the industrial revolution era 4.0. For this reason, community service activities with this community partnership program can be an alternative to helping the problems faced by the Girimakmur Village Government, Malangbong District, Garut Regency in utilizing integrated information and communication technology to serve various community needs by focusing on increasing work speed, improving data quality. and services, as well as accompanied by an increase in the dissemination of information to the public through the use of the website-based Girimakmur Village Administration and Service System (SALAD GM) application.